Application of diffusional kurtosis imaging to detect occult brain damage in multiple sclerosis and neuromyelitis optica. (7th September 2016) - Qian, Wenshu; Chan, Koon Ho; Hui, Edward S.; Lee, Chi Yan; Hu, Yong; Mak, Henry Ka‐Fung
Abstract : Multiple sclerosis (MS) and neuromyelitis optica (NMO) are two common types of inflammatory demyelinating disease of the central nervous system. Early distinction of NMO from MS is crucial but quite challenging. In this study, 13 NMO spectrum disorder patients (Expanded Disability Status Scale (EDSS) of 3.0 ± 1.7, ranging from 2 to 6.5; disease duration of 5.3 ± 4.7 years), 17 relapsing–remitting MS patients (EDSS of 2.6 ± 1.4, ranging from 1 to 5.5; disease duration of 7.9 ± 7.8 years) and 18 healthy volunteers were recruited. Diffusional kurtosis imaging was employed to discriminate NMO and MS patients at the early or stable stage from each other, and from healthy volunteers. The presence of alterations in diffusion and diffusional kurtosis metrics in normal‐appearing white matter (NAWM) and diffusely increased mean diffusivity (MD) in the cortical normal‐appearing gray matter (NAGM) favors the diagnosis of MS rather than NMO. Meanwhile, normal diffusivities and kurtosis metrics in all NAWM as well as increases in MD in the frontal and temporal NAGM suggest NMO. Our results suggest that diffusion and diffusional kurtosis metrics may well aid in discriminating the two diseases. Abstract : Diffusional kurtosis imaging was employed for discriminating neuromyelitis optica (NMO) and multiple sclerosis (MS) patients from each other and from healthy volunteers. Alterations in conventional diffusion and kurtosis metrics in normal‐appearing WM (NAWM) and diffusely increased mean diffusivity in cortical normal‐appearing GM (NAGM) would favor the diagnosis of MS rather than NMO. Meanwhile, normal diffusivities and kurtosis metrics in all NAWM with increases in mean diffusivity in frontal and temporal NAGM suggest NMO.